Genre-Based Aproach in L2 Writing Classroom - Rasyidah, Nur (Universitas Muhammadiyah Sidoarjo, 2019)
This conceptual paper is aimed at examining the application of genre theory to an L2 classroom in a local university in Malaysia in the learning of specialized vocabulary in a food writing course. All three types of genre theory will be discussed, namely literary, rhetoric and linguistic genre theory to give a holistic understanding of genre. This will allow the coverage of both similarities and differences through all disciplines, and subsequently inform the richness of these theories, how it can be applied, and the significance of using these genre theories in the ESL writing classroom. This paper will also discuss the relationship between genre approach and genre writing and its application in the food writing classroom.